Finance Technology Innovation in the Finance Sector: The Role of E-money on Increasing Tax Revenue - Raden Kusyeni; Pandoyo Pandoyo; Ratih Kumala; Mochamad Sofyan (Ilomata International Journal of Tax and Accounting, 2022)
The expanding versatility of people in general in monetary exercises wants to make monetary exchanges simpler, more compelling and effective yet at the same time protected in exchanges. The mechanical advancement that is the subject of the most recent review in Indonesia is Financial Technology (FinTech). The adjustment of the type of cash, both paper cash and coins started to be supplanted with electronic cash or ordinarily alluded to as E-cash. E-cash right now circling in Indonesia as OVO Cash, Shopee Pay, Gopay, Brizzi, Paytren, isaku, Dana, Linkaja, Flazz and others, is a type of money innovation to complete monetary exchange exercises, with the presence of E-cash. This cash is relied upon to help people in general in getting to monetary items and work with monetary exchanges and duty installment exchanges. Progresses in monetary innovation can make it more straightforward for citizens to make charge installments. The exploration technique utilized is unmistakable subjective strategy with writing survey. The motivation behind this exploration is to help the local area in making charge installments simpler and it is trusted that this electronic installment can expand charge income.